A genomic and proteomic analysis of surface proteins in bovine-adapted lineages of Staphylococcus aureus. Issue 7 (10th July 2020) - D. Drumm, Shauna; Owens, Rebecca; Mitchell, Jennifer; M. Keane, Orla
Abstract : In Ireland, Staphylococcus aureus is the most common cause of intramammary infection (IMI) in cattle with the bovine-adapted lineages CC151 and CC97 most commonly found. Surface proteins play a major role in establishing and maintaining the infection. A previous study revealed that a strain from the CC151 lineage showed significant decay in genes encoding predicted surface proteins. Twenty-three S. aureus strains, twelve belonging to CC151 and eleven belonging to CC97, isolated from clinical IMI, were sequenced and genes encoding cell wall anchored (CWA) proteins predicted. Analysis showed that a minority of genes encoding putative CWA proteins were intact in the CC151 strains compared to CC97. Of the 26 known CWA proteins in S. aureus, the CC151 strains only encoded 10 intact genes while CC97 encoded on average 18 genes. Also within the CC97 lineage, the repertoire of genes varied depending on individual strains, with strains encoding between 17-20 intact genes. Although CC151 is reported to internalize within bovine host cells, it does so in a fibronectin-binding protein (FnBPA and FnBPB) independent manner. In-vitro assays were performed and results showed that strains from CC151, and surprisingly also CC97, weakly bound bovine fibronectin and that the FnBPs were poorly expressed in both these lineages. Mass spectrometry analysis of cell wall extracts revealed that SdrE and AdsA were the most highly expressed CWA proteins in both lineages. These results demonstrate significant differences between CC151 and CC97 in their repertoire of genes encoding CWA proteins, which may impact immune recognition of these strains and their interactions with host cells.